2002
DOI: 10.1007/s00228-002-0468-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of suplatast tosilate, a Th2 cytokine inhibitor, on cough variant asthma

Abstract: Suplatast improved the cough scores and the cough threshold for capsaicin in patients with CVA without significant side effects, suggesting the effectiveness of suplatast in the treatment of CVA. Suplatast also decreased the percentage of eosinophils and concentrations of ECP in induced sputum, suggesting improvement in eosinophilic inflammation in patients with CVA. Further pharmacodynamic research is needed to explain the precise mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 13 publications
2
25
0
Order By: Relevance
“…The coughing induced by ACE inhibitors is often not responsive to antitussives. Also, it has been reported that suplatast is clinically effective for the treatment of chronic coughs such as cough associated with atopic cough and CVA [5,6]; this is consistent with the present electrophysiological findings.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The coughing induced by ACE inhibitors is often not responsive to antitussives. Also, it has been reported that suplatast is clinically effective for the treatment of chronic coughs such as cough associated with atopic cough and CVA [5,6]; this is consistent with the present electrophysiological findings.…”
Section: Discussionsupporting
confidence: 82%
“…It has also been reported that bakumondo-to is clinically effective against chronic cough in asthmatic patients with cough hypersensitivity [12,13]. Recently, it has been reported that suplatast improved the cough scores and the cough threshold for capsaicin in patients with CVA [6]. The coughing in patients with CVA has been found to be resistant to the treatment with other antitussive drugs [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some reports have shown that suplatast tosilate is an effective cough treatment [37, 38] because it improved airway cough hypersensitivity induced by airway allergy and cough by cough-variant asthma. Thus, suplatast tosilate may be an effective treatment for the cough associated with eosinophilic pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…Suplatast (suplatast tosilate, ((±)-[2-[4-(3-ethoxy-2-hydroxy-propoxy) phenylcarbamoyl] ethyl] dimethylsulfonium p-toluenesulfonate)) is a selective Th2 cytokine inhibitor [9] and improves the cough score and the cough threshold for capsaicin in patients with cough variant asthma [10]. Previously, we found that suplatast inhibits codeine-resistant coughs in guinea pigs with bronchitis or treated with an angiotensin-converting enzyme inhibitor [11].…”
Section: Introductionmentioning
confidence: 99%